Long‐term recovery In critical illness myopathy is complete, contrary to polyneuropathy. Issue 3 (14th July 2014) - Koch, Susanne; Wollersheim, Tobias; Bierbrauer, Jeffrey; Haas, Kurt; Mörgeli, Rudolf; Deja, Maria; Spies, Claudia D.; Spuler, Simone; Krebs, Martin; Weber‐Carstens, Steffen
ABSTRACT Introduction: Muscle weakness in critically ill patients after discharge varies. It is not known whether the electrophysiological distinction between critical illness myopathy (CIM) and critical illness polyneuropathy (CIP) during the early part of a patient's stay in the intensive care unit (ICU) predicts long‐term prognosis. Methods: This was a prospective cohort study of mechanically ventilated ICU patients undergoing conventional nerve conduction studies and direct muscle stimulation in addition to neurological examination during their ICU stay and 1 year after ICU discharge. Results: Twenty‐six patients (7 ICU controls, 8 CIM patients, and 11 CIM/CIP patients) were evaluated 1 year after discharge from the ICU. Eighty‐eight percent (n = 7) of CIM patients recovered within 1 year compared with 55% (n = 6) of CIM/CIP patients. Thirty‐six percent (n = 4) of CIM/CIP patients still needed assistance during their daily routine (P = 0.005). Conclusions: Early electrophysiological testing predicts long‐term outcome in ICU survivors. CIM has a significantly better prognosis than CIM/CIP. Muscle Nerve50: 431–436, 2014